Construction of high-resolution genetic maps of Zoysia matrella (L.) Merrill and applications to comparative genomic analysis and QTL mapping of resistance to fall armyworm. (December 2016) - Huang, Xiaoen; Wang, Fangfang; Singh, Ratnesh; Reinert, James; Engelke, M.; Genovesi, Anthony; Chandra, Ambika; Yu, Qingyi
Abstract Background Zoysia matrella, widely used in lawns and sports fields, is of great economic and ecological value.Z. matrella is an allotetraploid species (2n = 4x = 40) in the genus zoysia under the subfamily Chloridoideae. Despite its ecological impacts and economic importance, the subfamily Chloridoideae has received little attention in genomics studies. As a result, limited genetic and genomic information are available for this subfamily, which have impeded progress in understanding evolutionary history of grasses in this important lineage. The lack of a high-resolution genetic map has hampered efforts to improve zoysiagrass using molecular genetic tools. Results We used restriction site-associated DNA sequencing (RADSeq) approach and a segregating population developed from the cross betweenZ. matrella cultivars 'Diamond' and 'Cavalier' to construct high-resolution genetic maps ofZ. matrella . The genetic map of Diamond consists of 2, 375 Single Nucleotide Polymorphism (SNP) markers mapped on 20 linkage groups (LGs) with a total length of 1754.48 cM and an average distance between adjacent markers at 0.74 cM. The genetic map of Cavalier contains 3, 563 SNP markers on 20 LGs, covering 1824.92 cM, with an average distance between adjacent markers at 0.51 cM. A higher level of genome collinearity betweenZ. matrella and rice than that betweenZ. matrella and sorghum was revealed by comparative genomic analysis. Pairwise comparison revealed that two independent nested chromosome fusion events occurred afterZ. matrella and sorghum split from a common ancestor. The high-resolution linkage maps were applied into mapping QTLs associated with fall armyworm (FAW) resistance and six loci located on LGs 8 and 20 were detected to be significantly associated with FAW resistance. Conclusion The high-resolution linkage maps provide anchor points for comparative genomics analysis betweenZ. matrella and other grass species. Our comparative genomic analysis suggested that the chromosome number reduction from 12 to 10 had occurred independently via a single-step in the subfamilies Chloridoideae and Panicoideae. The high-resolution genetic maps provide an essential framework for mapping QTLs associated with economically and agronomically important traits. The major QTLs mapped on LG8 of the Cavalier map provide a starting point for cloning FAW resistance genes and further studies for a better understanding of FAW resistance in zoysiagrass.